New data on the fauna of China, part II: the millipede genus Nepalmatoiulus Mauriès, 1983 (Diplopoda, Julidae) in continental China and Taiwan, with descriptions of seven new species - Mikhaljova, Elena V. (Zootaxa, 2020)
Nepalmatoiulus is currently represented in continental China and Taiwan by twenty-five species. Seven new species of the genus are described from the China: Nepalmatoiulus lanpingensis sp. nov., Nepalmatoiulus uncinatus sp. nov., Nepalmatoiulus emarginatus sp. nov., Nepalmatoiulus deqenensis sp. nov., Nepalmatoiulus parvulus sp. nov., Nepalmatoiulus acutidentatus sp. nov., Nepalmatoiulus hexiensis sp. nov. Additional material for Nepalmatoiulus tianbaoshanensis Mikhaljova, 2020 is given. A key is given to all Nepalmatoiulus presently known from continental China and Taiwan Island. The distributions of Chinese and Taiwanese Nepalmatoiulus species are discussed. Taxonomic remarks are provided for nearly all new species.